2006
DOI: 10.1111/j.1742-4658.2006.05114.x
|View full text |Cite
|
Sign up to set email alerts
|

Proton‐decoupled 15N and 31P solid‐state NMR investigations of the Pf3 coat protein in oriented phospholipid bilayers

Abstract: The coat proteins of filamentous phage are first synthesized as transmembrane proteins and then assembled onto the extruding viral particles. We investigated the transmembrane conformation of the Pseudomonas aeruginosa Pf3 phage coat protein using proton‐decoupled 15N and 31P solid‐state NMR spectroscopy. The protein was either biochemically purified and uniformly labelled with 15N or synthesized chemically and labelled at specific sites. The proteins were then reconstituted into oriented phospholipid bilayers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…Notably, membranes of small hydrophobic thickness have been shown to promote a transmembrane alignment of other peptide sequences [55,66,67], and this experiment thereby provides a stringent test for the propensity of a sequence to traverse the bilayer. In-plane alignments have also been observed for many other sequences found in nature including antimicrobial peptides [40,49,[68][69][70][71][72][73][74][75][76], signal sequences [52], surfactant peptides [77], the amino-terminal membrane anchor of huntingtin [41] or a domain of the Herpes virus protein ICP47 [48] (Table 1). Furthermore, peptide sequences have been designed to orient along the membrane surface [78][79][80][81], and this design has been confirmed by solid-state NMR spectroscopy, for example, for [ 15 N-Leu7]-KL15 [15] (Table 1), which exhibits a chemical shift of 71 ± 5 ppm in di-20:1-PC lipid bilayers ( Figure 2D).…”
Section: Investigating the Membrane Interactions Of Polypeptides By Smentioning
confidence: 95%
See 1 more Smart Citation
“…Notably, membranes of small hydrophobic thickness have been shown to promote a transmembrane alignment of other peptide sequences [55,66,67], and this experiment thereby provides a stringent test for the propensity of a sequence to traverse the bilayer. In-plane alignments have also been observed for many other sequences found in nature including antimicrobial peptides [40,49,[68][69][70][71][72][73][74][75][76], signal sequences [52], surfactant peptides [77], the amino-terminal membrane anchor of huntingtin [41] or a domain of the Herpes virus protein ICP47 [48] (Table 1). Furthermore, peptide sequences have been designed to orient along the membrane surface [78][79][80][81], and this design has been confirmed by solid-state NMR spectroscopy, for example, for [ 15 N-Leu7]-KL15 [15] (Table 1), which exhibits a chemical shift of 71 ± 5 ppm in di-20:1-PC lipid bilayers ( Figure 2D).…”
Section: Investigating the Membrane Interactions Of Polypeptides By Smentioning
confidence: 95%
“…Several of these have been investigated by 15 N solid-state NMR spectroscopy and a transmembrane alignment confirmed (e.g. [34,[51][52][53][54]). These general features can be used to design much simpler domains such as sequences made solely of leucines or of mixtures of alanines and leucines [55][56][57][58][59][60][61].…”
Section: Investigating the Membrane Interactions Of Polypeptides By Smentioning
confidence: 99%
“…However, because this reflects the dynamics, mosaic spread and topological heterogeneity of the protein in the membrane, these spectra provide important information about the proteins' structure and functioning. [35] Indeed, at room temperature the hydrophobic domain of colicin E1 that encompasses helix 9 exhibits a broad range of orientations, topologies and/or conformations (Figure 3 A), but a more homogenous in-plane alignment upon freezing the sample is observed (Figure 3 B). These temperature-related differences could be due to a more superficial association of the protein with the bilayer at low temperature.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the signal intensities of more hydrophilic helices, which are probably only loosely or not at all membrane associated, remained too weak to be analyzed. Previously we and others have observed a large decrease in the 15 N solid-state NMR signal intensities of 15 N-labeled amides that are located within mobile loop regions, [35] or when part of helices that exhibit motions on an intermediate timescale. [24,[36][37][38] It has been suggested that this is due to motional averaging of the 1 H-15 N dipolar couplings, which interferes with efficient cross-polarization.…”
Section: Discussionmentioning
confidence: 98%
“…Although the analysis indicated a potential for structural studies using multidimensional experiments for uniformly 15 N-, and in particular 13 C, 15 N-labeled proteins of this size, it was also clear that a prerequisite for full structural analysis of uniformly labeled samples using oriented samples is that they align at least as well as demonstrated for a number of smaller membrane-bound peptides reconstituted into phospholipid bilayers (13,14,16,17). For many membrane proteins, however, such a high degree of alignment may be very hard to obtain, since imperfect alignment governed by mosaic spread appears to be an intrinsic property of a number of smaller peptides/proteins (33)(34)(35)(36), as well as for larger membrane proteins in native membranes (37). The key problem is that imperfect alignment translates into significant line broadening and thereby inevitably increases the risks for overlap of resonances, which cannot be resolved even using time-costly experiments with many spectral dimensions.…”
Section: Introductionmentioning
confidence: 99%